Do side payments help? Collective decisions and strategic delegation - Bård Harstad (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2007)
I investigate when side payments facilitate cooperation in a context with strategic delegation. On the one hand, allowing side payments may be necessary when one party's participation constraint otherwise would be violated. On the other, with side payments each principal appoints a delegate that values the project less, because this increases her bargaining power. Reluctant agents, in turn, implement too few projects. I show that side payments are bad if the heterogeneity is small while the uncertainty and the typical value of the project are large.With a larger number of parties there may be a stalemate without side payments, but delegation becomes more strategic as well, and cooperation decreases in either case
Keywords: C78; D78; F53; H77; 330; Gruppenentscheidung; Kompensationslösung; Prinzipal-Agent-Theorie; Theorie